Specific Aspects of Uzbekistan's Way of Evolutionary Development - Shahzoda Yusupova; Abrar Turayev (Genius Journals, 2023)
This article shows the path of development of the Republic of Uzbekistan in the years of independence, the principles of statehood and social development and their gradual improvement.
Keywords: independence; Uzbek model; strategy; action strategy